Effect of Zeolite Spreading Frequency on Litter Base to Housing Quality of Broiler - Pattiselanno, F; Randa, SY (ANIMAL PRODUCTION, 2005)
The research was aimed to investigate the application of zeolite spreading frequency in related to control housing quality.  In this study, three aspects of quality were observed namely housing temperature, litter temperature and litter humidity.  The result indicated that spreading frequency was only significant effective in controlling litter humidity.  Treatment of P3 significantly (P<0.05) reduced humidity level of litter base from 42.83% (P0) to 31.18%. (Animal Production 7(2): 81-88 (2005) Key Words: Quality, Broiler, Zeolite, Spreading, Litter